PENGARUH BEBAN DAN STRES KERJA TERHADAP PRODUKTIVITAS DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT PAL INDONESIA, SURABAYA - Laili, Wahdatul; Wildan, Muhammad Alkirom (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
The purposes of this study are to determine the effect of workload and stress on productivity through motivation as an intervening variable on employees of PT PAL Indonesia, Surabaya. It uses a quantitative method that data were collected by distributing the questionnaires to a number of employees of PT PAL Indonesia. The population was 1,553 employees and the sample is 94 employees determined based on the Slovin formula. Using SmartPLS as data analysis tool, the results showed that (1) Workload has a positive and significant effect on productivity is 0.187 and a significance value is 0.047 (2) Workload has a positive and significant effect on motivation of 0.258 and a significance value is 0.008 (3) Workload has a positive and insignificant effect on productivity is 0.169 and a significance value of 0.119 (4) Work stress has a positive and significant effect on motivation is 0.451 and a significance value is 0.000 (5) Motivation has a positive and significant effect on productivity of 0.419 and a significance value is 0.000 (6) Workload has a positive and significant effect on productivity through motivation is 0.108 and a significance value is 0.047 (7) Work stress has a positive and significant effect on productivity through motivation is 0.189 and a significance value is 0.002.